Strategi Komunikasi dalam Penguatan Infrastruktur di Daerah Terpencil - Arni Damayanti; Putri Dwi Hastuti; Ellisya Taskiyah (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
This research aims to analyze the communication strategies implemented in strengthening infrastructure in remote areas and the challenges faced in this process. Remote areas often face difficulties in terms of access to information, limited technology, and low community participation in development projects. The research method used is qualitative with a case study approach, involving in-depth interviews, field observations and documentation analysis. The research results show that effective communication strategies include the use of traditional communication channels, language simplification, and community involvement in every stage of the project. Challenges faced include limited access to technology, cultural barriers, and low levels of education, which can be overcome with approaches based on local context and information transparency. This research provides recommendations for increasing the effectiveness of communication in strengthening infrastructure in remote areas, in order to obtain maximum support from the community and ensure project success.